DETERMINAN NILAI PERUSAHAAN TERHADAP SEKTOR CONSUMER NON CYCLICALS - Wachidah Fauziyanti; Sarbullah Sarbullah; Lia Anisatul F (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2023)
Firm value is a certain condition that has been achieved by a company as an illustration of public trust in the company after going through a process of activity for several years. This study aims to determine the effect of capital structure, company growth and profitability on firm value in consumer non-cyclicals sector companies. listed on the Indonesia Stock Exchange in 2019-2021.The population in this study is consumer non-cyclicals sector companies listed on the main board index of the Indonesian Stock Exchange totaling 57 companies. The sample in this study used purposive sampling so that a sample of 30 companies was obtained. Methods of data analysis using multiple linear regression analysis. Based on the results of data analysis it was concluded that capital structure has a significant effect on firm value, company growth has no significant effect on firm value, Profitability has no significant effect on firm value. Suggestions and conclusions for future researchers are advised to examine other factors that are thought to influence the occurrence of firm value.